2017
DOI: 10.1007/s00405-017-4772-8
|View full text |Cite
|
Sign up to set email alerts
|

Tubomanometry value as an associated factor for medication outcomes in adult acute otitis media with effusion

Abstract: Tubomanometry (TMM) is a relatively novel method for testing the eustachian tube (ET) function, which is speculated to be closely related to otitis media with effusion (OME). The purpose of this study is to explore the predictive power of TMM value for medication outcomes in adult acute OME. A cohort of 41 adult acute OME patients with 53 affected ears was studied retrospectively. All these patients completed a 2-week treatment including oral Myrtol Standardized Enteric capsules, nasal steroid, and oral antihi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
0
11
0
1
Order By: Relevance
“…Patients who had fluid behind the eardrum (Type B Tympanogram) were less likely to respond than those with retracted eardrums (Type C Tympanogram). 17,18 NonPharmacological Treatment. In two studies, the Politzer device was analyzed among 63 patients with subacute or duration-unspecified ETD and improved symptoms in 30% of cases.…”
Section: Medical Therapy Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients who had fluid behind the eardrum (Type B Tympanogram) were less likely to respond than those with retracted eardrums (Type C Tympanogram). 17,18 NonPharmacological Treatment. In two studies, the Politzer device was analyzed among 63 patients with subacute or duration-unspecified ETD and improved symptoms in 30% of cases.…”
Section: Medical Therapy Resultsmentioning
confidence: 99%
“…Of the 12 studies included in our systematic review, 9 were quantitatively assessed with meta-analysis to analyze outcomes among 527 patients with ETD. Meta-analysis of weighted proportion for symptomatic improvement was conducted among five patient cohorts 17,18,29 and found that at ≤2 weeks follow-up, 50.3% (95% CI, 41.7-59.0) of patients improved with MM. Meta-analysis of continuous measures for ETDQ-7 resulted in À0.88 (95% CI, À1.12 to À0.64), favoring improvement of patient-reported scores.…”
Section: Meta-analysis Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…В свою очередь, наличие разреженного воздуха и персистирующее воспаление в барабанной полости способствуют обструкции слуховой трубы, формируя порочный круг. Кроме того, отрицательное давление приводит к образованию ретракционного кармана барабанной перепонки, холестеатомы и последующей кондуктивной тугоухости [3][4].…”
Section: Introductionunclassified